On the Fresnel integrals and the convolution - Adem Kiliçman (International Journal of Mathematics and Mathematical Sciences, 2003)
The Fresnel cosine integral C(x), the Fresnel sine integral S(x), and the associated functions C+(x), C−(x), S+(x), and S−(x) are defined as locally summable functions on the real line. Some convolutions and neutrix convolutions of the Fresnel cosine integral and its associated functions with x+r and xr are evaluated.